2022
DOI: 10.3390/min12101326
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Detection Techniques, Health Hazards and Human Health Risk Assessment of Arsenic Pollution in Soil and Groundwater

Abstract: One of the most significant elements in the environment is arsenic (As). It is a hazardous metalloid that causes contamination of soil and water supplies as a result of numerous anthropogenic and natural sources. This pollution has detrimental impacts on human health and the ecosystem, making it crucial to monitor and control. The release of As from minerals into the soil and groundwater depends on the kind of mineral, pH, and redox conditions. As is typically found in two forms, trivalent arsenic (As3+, arsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 163 publications
0
9
0
Order By: Relevance
“…Arsenic proved a popular topic for element-specific reviews with no fewer than three being published during the period covered by this ASU. With reference to soils and waters, both Patel et al 99 (238 references) and Valskys et al 100 (177 references) discussed As contamination, quantification, sources, mobility and health hazards. Mihucz 101 (222 references) focused on As speciation and analysis in soil, water, foods and Ayurvedic medicines.…”
Section: Analysis Of Soils Plants and Related Materialsmentioning
confidence: 99%
“…Arsenic proved a popular topic for element-specific reviews with no fewer than three being published during the period covered by this ASU. With reference to soils and waters, both Patel et al 99 (238 references) and Valskys et al 100 (177 references) discussed As contamination, quantification, sources, mobility and health hazards. Mihucz 101 (222 references) focused on As speciation and analysis in soil, water, foods and Ayurvedic medicines.…”
Section: Analysis Of Soils Plants and Related Materialsmentioning
confidence: 99%
“…Arsenic is a harmful element that is found everywhere and has become more concentrated in water and soil as shown in Figure 3 ( 136 , 137 ). It can be found in inorganic, organic, pentavalent, and trivalent forms, and it can combine with a wide range of elements, including Pb, O, H, Cu, and S ( 31 , 138 ). Similar to human exposure, cattle in As-affected areas are also exposed to hazardous quantities of the metal ( 6 , 107 ).…”
Section: Heavy Metals: Their Toxicity Mechanism and Effectsmentioning
confidence: 99%
“…Inorganic trivalent arsenic (AS 3+ ) and pentavalent arsenic (As 5+ ) exhibit significantly different acute toxicity and biological processes. The renal tubules actively transport arsenate (As 5+ ), and a minor portion of this form is converted to AS 3+ , the molecule that is more acutely poisonous ( 138 , 167 ). It was concluded that the formation of renal toxicity by As exposure causes major kidney problems in cattle influenced by oxidative stress and lipid peroxidation ( 167 169 ).…”
Section: Heavy Metals: Their Toxicity Mechanism and Effectsmentioning
confidence: 99%
“…As is a chemical found in the environment that has a significant impact on the health of animals, including poultry ( 76 ). As can be found in trivalent, pentavalent, organic, and inorganic forms and can combine with variety of elements, such as S, H, O, Pb, and Cu ( 31 , 77 ). Similar to animal exposure more generally, poultry in As-affected areas are exposed to dangerous level of the toxic metal ( 78 ).…”
Section: Sources Of Heavy Metal Transmission and Their Impact On Poultrymentioning
confidence: 99%